Gallbladder wall thickening as a sign of esophageal varices in chronic liver disease* - , Galip ERSÖZ, Ömer ÖZÜTEMİZ and , Ulus Salih AKARCA and , Mustafa YILMAZ and , Zeki KARASU and , Yücel BATUR (Turkish Journal of Gastroenterology 1, 2019)
-